2016
DOI: 10.1186/s12889-016-2999-8
|View full text |Cite
|
Sign up to set email alerts
|

The association between exposure and psychological health in earthquake survivors from the Longmen Shan Fault area: the mediating effect of risk perception

Abstract: BackgroundIn this study, exposure refers to survivors who suffered from life-changing situations, such as personal injuries, the deaths or injury of family members, relatives or friends or the loss of or damage to personal or family property, as a result of the earthquake. The mediating effect of risk perception on the exposure and psychological health in survivors from the Longmen Shan Fault area and the moderating effect of social support on the relationship between risk perception and psychological health w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…For example, the government could establish an emergency risk communication management system to help people to avoid or mitigate the negative impact of COVID-19 on their mental health by controlling risk perception levels, especially perceived controllability of risk. 48 As to building reasonable risk perception, it is important to provide the public with authentic and accurate information and control the contagious disease outbreaks as soon as possible. 49 , 50 On the other hand, social support should be paid more attention to when conducting psychological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the government could establish an emergency risk communication management system to help people to avoid or mitigate the negative impact of COVID-19 on their mental health by controlling risk perception levels, especially perceived controllability of risk. 48 As to building reasonable risk perception, it is important to provide the public with authentic and accurate information and control the contagious disease outbreaks as soon as possible. 49 , 50 On the other hand, social support should be paid more attention to when conducting psychological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Minor depression and anxiety can account for short-term mental health problems that are likely to develop into chronic forms, such as PTSD, in later stages. 4,[16][17][18] Medical personnel 19 and professional disaster workers 20 in particular were reported as being more exposed to emotionally traumatic events during disaster response, such as injuries, losses incurred by disaster victims, violence, deaths, separation, and grief. Relating to this, PTSD emerged amongst the literature as a common long-term outcome of trauma exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies have shown that participants with higher level of psychological distress, such as anxiety, depression, and fear, are more likely to develop PTSD symptoms (Wang et al, 2020b; Xi et al, 2020). This may be because people fear injury and death, especially under unexpected and unprepared situations, which can create panic, fear, and tension (Xu et al, 2016). Since the events are unexpected, people will feel confused about their current situation, and they will be uncertain about their future (Yates and Stone, 1992).…”
Section: Introductionmentioning
confidence: 99%